The long noncoding RNA DLGAP1‐AS2 facilitates cholangiocarcinoma progression via miR‐505 and GALNT10. Issue 2 (31st December 2020) - Liu, Zhao; Pan, Lili; Yan, Xiaofang; Duan, Xiuna
Abstract : Cholangiocarcinoma (CCA) is a highly invasive malignant tumor with high mortality. Most cases of CCA are already advanced when they are detected, resulting in poor prognosis. As such, there is an ongoing need for the identification of effective biomarkers for CCA. The long noncoding RNA DLGAP1‐AS2 has been reported to have prognostic value in glioma and Wilms' tumor. Here, we investigated the function of DLGAP1‐AS2 in CCA. The differential expression of DLGAP1‐AS2 in CCA tissues and normal tissues was first examined using data from the The Cancer Genome Atlas database and then in CCA cell lines by quantitative RT‐PCR (qRT‐PCR). The target gene was predicted by bioinformatics analysis, and the binding sites were confirmed using luciferase assay. DLGAP1‐AS2 is up‐regulated in CCA, and high DLGAP1‐AS2 expression promotes cell viability and is associated with poor prognosis. Notably, DLGAP1‐AS2 acts as a sponge to suppress miR‐505 expression, and miR‐505 reduces the expression of N ‐acetylgalactosaminyltransferase 10 (GALNT10) in CCA cells. Biofunctional experiments revealed that a miR‐505 inhibitor almost completely removed the inhibitory effect of si‐DLGAP1‐AS2 on CCA cell malignant progression, whereas the malignant phenotype of cells cotransfected with si‐DLGAP1‐AS2 and si‐GALNT10 was significantly reduced as compared with the control. In summary, the DLGAP1‐AS2/miR‐505/GALNT10 axis may contribute to regulating the malignant progression of CCA and may have potential as a novel target for CCA therapy. Abstract : The long noncoding RNA DLGAP1‐AS2 facilitates the malignant progression of cholangiocarcinoma via miR‐505 and GALNT10 and may have potential as a novel target for cholangiocarcinoma therapy.